Brucella abortus Infection Elicited Hepatic Stellate Cell-Mediated Fibrosis Through Inflammasome-Dependent IL-1β Production - Arriola Benitez, Paula Constanza; Pesce Viglietti, Ayelén Ivana; Gomes, Marco Tulio R.; Oliveira, Sergio Costa; Quarleri, Jorge Fabián; Giambartolomei, Guillermo Hernán; Delpino, María Victoria (Frontiers in Immunology, 2020)
In human brucellosis, the liver is frequently affected. Brucella abortus triggers a profibrotic response on hepatic stellate cells (HSCs) characterized by inhibition of MMP-9 with concomitant collagen deposition and TGF-β1 secretion through type 4 secretion system (T4SS). Taking into account that it has been reported that the inflammasome is necessary to induce a fibrotic phenotype in HSC, we hypothesized that Brucella infection might create a microenvironment that would promote inflammasome activation with concomitant profibrogenic phenotype in HSCs. B. abortus infection induces IL-1β secretion in HSCs in a T4SS-dependent manner. The expression of caspase-1 (Casp-1), absent in melanoma 2 (AIM2), Nod-like receptor (NLR) containing a pyrin domain 3 (NLRP3), and apoptosis-associated speck-like protein containing a CARD (ASC) was increased in B. abortus-infected HSC. When infection experiments were performed in the presence of glyburide, a compound that inhibits NLRP3 inflammasome, or A151, a specific AIM2 inhibitor, the secretion of IL-1β was significantly inhibited with respect to uninfected controls. The role of inflammasome activation in the induction of a fibrogenic phenotype in HSCs was determined by performing B. abortus infection experiments in the presence of the inhibitors Ac-YVAD-cmk and glyburide. Both inhibitors were able to reverse the effect of B. abortus infection on the fibrotic phenotype in HSCs. Finally, the role of inflammasome in fibrosis was corroborated in vivo by the reduction of fibrotic patches in liver from B. abortus-infected ASC, NLRP, AIM2, and cCasp-1/11 knock-out (KO) mice with respect to infected wild-type mice.